External Loop Recorders: Primary Care Placement Is Noninferior to Hospital-Based Cardiac Unit - Kara J. Callum; Lynn Hall; Sharon Jack; Colin Farman; Gordon F. Rushworth; Stephen J. Leslie (SAGE Publishing, 2020)
Introduction: External loop recorders (ELRs) are recommended for the investigation of syncope and palpitations. This study aimed to compare rates of arrhythmia detection between primary care (PC) and hospital-based cardiac unit (HBCU) fitted ELRs. Methods: Data were captured from January to December 2015. Twenty-eight general practitioner practices and 1 hospital took part. Patients were divided into those with ELR fitted in PC or HBCU. All ELR data were analyzed by a cardiac physiologist. Results: A total of 560 ELR recordings were analyzed; 219 (PC) versus 341 (HBCU). There was no difference between the baseline characteristics (all P s > .05). The predominant indication for ELR in each group were palpitations; between-group variation was observed for syncope ( P = .0004). There were no significant between-group differences in the number of recordings per patient; however, PC group wore the ELR for less time (median 7 days vs median 14 days; P < .0001). There were no differences in arrhythmia detection between PC- and HBCU-fitted ELRs (16.2% [n = 39] vs 21.7% [n = 74], respectively; P = .28). PC placement of ELRs was highest in very remote rural communities ( P = .005) and correlated with distance from HBCU ( r = 0.39; P = .04). Conclusions: This study showed no difference in detection of arrhythmias between PC and HBCU fitted ELRs. This suggests adequate ELR recording can be completed by suitably trained staff in PC. Furthermore, ELRs were fitted for less time in PC without an adverse effect on diagnostic yield. ELR usage increased with increasing distance from the specialist center and rurality suggesting improved local access to arrhythmia detection services.